The Diamond Life
The Revolutionary United Front's (RUF) attack on Freetown in January of 1999 was the culmination of a decade-long and bloody struggle between the RUF and the government of Sierra Leone. The rebel forces, bolstered by the former Sierra Leonean Army, which had turned on the government, swept into the city, killing, mutilating, and raping thousands in the continuing war over the control of the country's rich diamond fields. RUF units burned houses with civilians inside, shot and raped people at random, killing an estimated 6,000 people in the span of three weeks. Since 1990, half the country's population of five million has been displaced. Today, Sierra Leone produces more refugees than any other country in Africa. The country is full of war victims, whose amputated limbs serve as living testimony to the brutality of the rebels. This Rights Alert feature, with footage and commentary by Sierra Leonean journalist Aroun Rashid Deen and music by Peter Gabriel, provides a disturbing glimpse into the greed and violence that fuels the diamond war. A Guerilla News Network production in association with WITNESS.